2020
DOI: 10.5114/jcb.2020.92913
|View full text |Cite
|
Sign up to set email alerts
|

A history of transurethral resection of the prostate should not be a contra-indication for low-dose-rate 125I prostate brachytherapy: results of a prospective Uro-GEC phase-II trial

Abstract: Purpose: Early reports suggested that transurethral resection (TURP) prior to permanent seed brachytherapy (BT) results in high incontinence rates. Guidelines consider prior TURP as a contra-indication to treatment, but improvements in imaging and treatment planning may reduce this risk, and are investigated in this prospective study. Material and methods: 99 men with histologically proven low-to intermediate-risk, localized prostate cancer, with a history of TURP performed at least 3 months before BT procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Other authors did not specify any technical problem to perform the BrT procedure (12,22). Salembier et al in a multicenter prospective analysis showed that it was possible to respect dosimetry constraints for BrT after a previous TURP, what had already been suggested by Cesaretti et al (19,24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors did not specify any technical problem to perform the BrT procedure (12,22). Salembier et al in a multicenter prospective analysis showed that it was possible to respect dosimetry constraints for BrT after a previous TURP, what had already been suggested by Cesaretti et al (19,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, urinary incontinence (UI) has been previously described as a major concern for patients who underwent TURP after BrT (11e17). History of TURP also used to be a relative contraindication because of increased risk for UI (or because of too large resected area for seed placement); however, experienced teams have conducted studies concluding that selected patients with prior TURP could undergo BrT without increased morbidity (18,19). Recent studies also suggest that patients with severe baseline lower urinary tract symptoms could safely undergo BrT by a skilled practitioner (20).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have reported the clinical outcomes of the LDR brachytherapy for patients with PC with TUR history. A single‐arm prospective study showed favorable oncological outcomes and acceptable urinary toxicity in patients with low to intermediate‐risk PC 3 . In contrast, a higher frequency of urinary toxicities was observed in patients with TUR history compared with those without it 4,5 .…”
mentioning
confidence: 99%
“…In contrast, a higher frequency of urinary toxicities was observed in patients with TUR history compared with those without it 4,5 . Additionally, the presence of a rim of the prostate tissue of at least 1 cm around the urethral defect at the posterolateral side was one of the inclusion criteria for seed implantation 3 …”
mentioning
confidence: 99%
“…For patients that fail alpha-1 adrenergic receptor antagonists and/or 5-alpha reductase inhibitor medication, Transurethral Resection of the Prostate (TURP) or a derived variant of this procedure, is often prescribed. The role of pretreatment TURP portending for genitourinary toxicity post definitive LDR brachytherapy or IMRT has been dismissed in select series (40)(41)(42)(43). The data regarding pre-existing TURP after SBRT is currently emerging, with mixed findings that appear dependent, in part, on dose (44,45).…”
mentioning
confidence: 99%